Dechema chemistry data series : heat of mixing data collection 2 binary and multicomponent systems - Christensen, C.; Gmehling, J.; Rasmussen, P.; Weidlich, U. (Dechema Frankfurt, 1984)
part 2
Keywords: Mixing -- tables, etc